Utilization of Senjang in Teaching Language and Cultural Preservation in the Digital Era - Indrasari, Noviastuti Putri; Setiawan, Ibnu Eko; Suprobo, Ganggas Dwi Woro (SEAMEO SEAMOLEC, 2024)
Senjang is an oral tradition of cultural practices and a representation of the people of Musi Banyuasin, South Sumatra. In today's digital era, oral literature has eroded because of technological advances. Therefore, steps must be taken to keep Senjang alive in society. By utilizing digital technology, this research will observe how effective TikTok and Instagram Reels are in teaching Senjang in a school environment. In both social media applications, users will collaborate with other users through the Stitch tool. One person makes the video, and others will most likely respond, and so on. This research is done by giving special treatment to the students to achieve specific goals, namely by giving assignments with digital applications that aim to improve students' oral literary abilities. The study results show that direct practice has a good effect on students and increases students' self-confidence. In addition, using social media is a means of promoting literacy, especially Senjang.